Determinants of non-use of family planning methods by young married women (15-24 years) living in urban slums of Uttar Pradesh - Yadav, Kriti; Agarwal, Monika; Singh, Jai Vir; Singh, Vijay Kumar (Indian Journal of Community Health, 2017)
Background: Total fertility rate of Uttar Pradesh is 2.7 with annual growth rate of 16.5. Age specific marital fertility rate (ASMFR) in Uttar Pradesh is highest in the age group of 20-24 years (383.9) followed by 15-19 years (271.0) age group. Use of contraceptives is also very low in this most productive age group. Among the Young married women in the age group of 15-24 years the contraceptive prevalence rate (CPR) is only 27.75% which is quite low than the target CPR of 60%. State level data presents a grim picture of contraceptive use in the slum areas in comparison to non-slum areas. This slum population is the most vulnerable section of our society. Aims & Objectives: i) To assess the prevalence of non-use of contraceptives among young married women living in urban slums. ii) To understand the reasons for non-use of contraceptives among young married women. iii) To explore the factors influencing non-use of contraceptive among young married women. Materials and Methods: A cross sectional study was carried out in the urban slums of Lucknow. Out of the eight Nagar-Nigam zones in Lucknow, one Urban-Primary Health Centre was selected randomly from each zone. From each Urban- Primary Health Centre, 2 slums were selected randomly. In selected slum, all the households were visited until at least 33 young married women (15-24 years) were interviewed using a pre-tested questionnaire to obtain the desired sample size of 535. The data was analyzed using SPSS 16.0. Results: Current use of contraceptives was found to be 33.8 % and almost two-thirds (66.2%) of the participants were not using any form of contraceptive method. The important reasons for non-use of contraception were embarrassment / hesitancy / shyness regarding family planning, lack of knowledge about the contraceptive method or place of availability of services, opposition to contraceptive use by husband or family members and women’s desire to get pregnant. About one third of the women had no perceived need for contraception. Among the various bio-social and fertility related variables, educational attainment of the women, employment status, parity, autonomy of the women, attitude of the husband towards family planning, motivation to adopt contraceptive and contact with ANM during home visits were the prime independent predictors for non-use of contraceptives. Conclusion: The study found contraceptive use to be very low among the young married women. The findings showed that motivation of women to adopt family planning method through counseling along with provision of youth friendly services are needed to be address to achieve improvement in contraceptive use among these young married women living in urban slums.